Efficacy of logbook as a clinical assessment: Using DOPS evaluation method - Shahzad Mehranfard; Ferdos Pelarak; Hamideh Mashalchi; Leila Kalani; Leila Masoudiyekta (Shahrekord University of Medical Sciences, 2022)
Background and aims: Clinical learning has a vital role in nursing. Appropriate methods should be used to evaluate the quality of clinical learning. For performance-based evaluation of nursing students, the effect of logbooks in an internship was investigated using the direct observation of procedural skills (DOPS) method. Methods: This experimental study was performed on 80 second-semester nursing students by randomly assigning samples to two intervention and control groups at Dezful University of Medical Sciences in 2019. The logbook was used for the experimental group students, and the control group completed the internship without using a logbook. At the end of the internship, the students of two groups were evaluated by five procedures: changing the dressing, blood pressure control, IV catheterization, Intramuscular injection, and inserting a Foley catheter by DOPS test. Data were analyzed using qualitative and analytic statistics content analysis that was carried out using SPSS version 21 software. Results: The mean score of DOPS in the intervention group was 7.66±1.07, and in the control group, 6.74±0.86, Which indicates that the mean score of the intervention group is 0.92 points higher than the mean score of the control group. In general, the scores of all clinical skills except inserting a Foley catheter in the intervention group were higher than the control group. However, this difference was significant only in two procedures. Conclusion: The results of this study showed that the logbook and evaluation could increase clinical skills and collegians' more profound learning and be effective in a professional and influential workforce.